2020
DOI: 10.1192/bjo.2020.36
|View full text |Cite
|
Sign up to set email alerts
|

Carers’ views on autism and eating disorders comorbidity: qualitative study

Abstract: Background Patients with co-occurring anorexia nervosa and autism respond differently to eating disorder treatments. Previous interviews with patients with both conditions and clinicians working in eating disorder services has highlighted service and treatment adaptations might be beneficial and could improve outcomes for these individuals. Aims The aim of this study was to explore carers’ experiences of current treatment approaches for people with autism who have anorexia nervosa, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 34 publications
5
53
0
Order By: Relevance
“…The interviews were initiated using a pre-developed interview schedule, based on previous research [22,28,32] that exploredcarers needs by research team. This schedule was then revised iteratively over the course of the interviews to follow the concerns of participants.…”
Section: Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interviews were initiated using a pre-developed interview schedule, based on previous research [22,28,32] that exploredcarers needs by research team. This schedule was then revised iteratively over the course of the interviews to follow the concerns of participants.…”
Section: Data Collectionmentioning
confidence: 99%
“…This study similarly found that ASC and AN were highly interrelated and potentially associated with unique treatment needs compared to people with AN only, such as requiring support around sensory di culties and longer time in treatment. Although Adamson & Kinnaird, et al (2020) focused on carer views on treatment adaptations for their loved ones, the ndings indicated that the carers themselves experience high levels of unmet needs, a perceived lack of support from existing services, and subsequent feelings of isolation and frustration. This study suggested that this group may potentially bene t from support designed speci cally for carers of people with ASC and AN.…”
mentioning
confidence: 99%
See 3 more Smart Citations